POLD1 Germline Mutations in Patients Initially Diagnosed with Werner Syndrome. Issue 11 (6th August 2015) - Lessel, Davor; Hisama, Fuki M.; Szakszon, Katalin; Saha, Bidisha; Sanjuanelo, Alexander Barrios; Salbert, Bonnie A.; Steele, Pamela D.; Baldwin, Jennifer; Brown, W. Ted; Piussan, Charles; Plauchu, Henri; Szilvássy, Judit; et al.
<x xml:space="preserve">Abstract</x> We have systematically analysed the POLD1 gene in 50 patients initially diagnosed with Werner Syndrome in whom no mutations in the Werner helicase gene were identified. Indeed, we found eight patients with heterozygous POLD1 mutations, thereby identifying the most common molecular cause of atypical Werner Syndrome until now. In addition, we could more than double the overall number of progeroid patients with POLD1 mutations, which allowed to substantially expand and modify the clinical characterization of this new example of a segmental progeroid disorder.